Reforming a pension security system for rural population - Petrukha, S.; Petrukha, N.; Hudenko, O.; Mazur, A.; Demydonok, I. (Університет «КРОК», 2021)
The current Ukrainian pension system has long been unable to perform the primary function laid on it –the social protection of the pension-age population, accordingly, the article is devoted to identifying a level of the pension security of the rural population in Ukraine. It reveals practical coordinates of primary factors of reforming the national pension security, namely, a structure of pensioners, dynamics of pension payments and wages of the rural population and by region.Purpose of the article is to study the problems and opportunities of reforming the pension system for the population in rural areas.Existing projects are analyzed, for implementing an accumulative pension system as well as sources of its financing in the future. It is set that ageing of the population is a negative trend in the demographic situation in Ukraine focusing for a long time on increasing a share of pension-age citizens and, accordingly, decreasing a share of the able-bodied population and younger age group population.Special attention is also paid to assessing possible improvement of pension payments of the rural population by implementing an accumulating pension tier of the pension system under existing projects for such a system (of the Ministry of Social Development of Ukraine and Ministry of Finance of Ukraine). Attention is focused on a “roadmap” of the development of the accumulative pension system, worked out by the Ministry of Finance of Ukraine, and built on “two pillars” –implementing the second tier of pension insurance (obligatory accumulative system) and developing voluntary pension accumulations. And the basic change vectors provided by the reform are modernizing pensions, a fair solidary system, obligatory annual indexation, overcoming a deficit of the Pension Fund of Ukraine.As of today, a problem of the efficient pension security is the acutest one for the whole state and not in terms of the rural population only. And a situation with the COVID-19 global pandemic only strengthens financial-economic turbulences. For this reason, it is emphasized in the article as a common thread that Ukraine will have a growing problem associated with pension payments, if there are no decisive, and sometimes also radical actions in terms of reforming the pension system. As solving this issue is associated with an important task –ensuring social protection of the population
Keywords: pension reform; rural population; accumulative tier; agriculture; пенсійна реформа; сільське населення; накопичувальний рівень; сільське господарство